Kisaran Inang Bean Common Mosaic Virus (Bcmv) Penyebab Penyakit Mosaik Pada Tanaman Kacang Panjang (Vigna sinensis L.) - A. A. GEDE PUTRA ADHITYA; I GEDE RAI MAYA TEMAJA; NI NENGAH DARMIATI; I DEWA NYOMAN NYANA; GEDE SUASTIKA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Host range of Bean Common Mosaic Virus (BCMV) causal agent of mosaic diseases on long yard bean (Vigna sinensis L.) This objective of the study is order to find out the host range of BCMV and symptom variation. DAS-ELISA (Double Antibody Sandwich-Enzyme Link Immunosorbent Assay) menthod was used in this study. The study consisted of (1) Host range evaluation by mechanical inoculation, (2). Symptom observation on tested plants, (3) Serological test with DAS–ELISA. The result indicated that BCMV can infected Leguminoceae plants (peanuts, long yard beans, and beans); Solanaceae plant (tomatoes); Cucurbetaceae plant (cucumbers); Amaranthaceae plant (spinach); and Balsaminaceae plant (henna flowers). DAS-ELISA analysis shown that those plants were infected by BCMV. The symptoms variation were mosaic, vein banding, wrinkled, and curved on commercial long yard beans (aura and panah merah varieties); wrinkled on commercial long yard beans (KPK and pusaka hijau varieties), cucumber and spinach; wrinkled and rolled on beans; wrinkled and curved upside on henna flowers. Key word : bean common mosaic virus , long yard beans, DAS-ELISA